(untitled) (Pedagogy of Higher and Secondary Education, 2006)
In the article the story goes about the problem of the down level of private needs and wishes of a person in using means of physical culture nowadays. Society’s needs, which are directed on a personality, but not on the level of his/her physical development, run out to be the motivating, factor in energization of his/her physical activity.